(3CbQGHGPjf JbGSje GdYdds - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd GHhHcQ eMeO Hf RcQjG GdQGRj QMeg Gddg(B: (3Cfj CPcQ aj cJGHj gPG GdCOhjI GdeQcHI GdJj GdMGLI EdjgG Ohf ZjQgG s
(3BNQgG (B:s
(3bO ChOYJ cJGHj gPG ef GdCOhjI GdeDdaI eG YGdLJ Hg ef GdCSbGe hGdCYdGd hde CVf hde CHNd HJYQja GdeJWHjjf hGddg GdeMehO Ydi Pdc hgh MSHj hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B237 - (3U(B249s
(3GfXQg eY HSJGf GdCWHGA HQbe (B349 -351s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
GAL - (3GdLRA (B1 - (3U (B267 ; GALS - (3GdLRA (B1 - (3U (B417 ; GALS - (3GdLRA (B3 - (3U (B291 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B30 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs